Soziale Beziehungen und Leistungsmotivation Die Bedeutung von Bezugspersonen für die längerfristige Aufrechterhaltung der Lern- und Leistungsmotivation - Looser, Dölf (Beiträge der Schweizer Bildungsforschung, 2011)
The author deals empirically with the question of what role social relationships with parents and teachers play in motivating children and adolescents to learn and perform. In particular, the question of the long-term development of achievement motivation over a period of 20 years is at the centre of attention, partly determined by the prevailing social bond in adolescence to the persons referred to and the achievement motivation of the young people themselves.